PENGARUH SALURAN PENJUALAN DAN KUALITAS PRODUK TERHADAP LOYALITAS PELANGGAN (Studi Kasus Pabrik Tahu Bapk Tarwoto di Nagari Kurnia Selatan, Kec. Sungai Rumbai) - Ike Frandika Wibowo; Yesi Gusteti; Kelik Purwanto (MANAJEMEN DEWANTARA, 2022)
Researchers want to see how far the influence of sales channels and product quality on customer loyalty. This study was conducted to find out and analyze what kind of influence is caused by sales channels and product quality on customer loyalty at the tofu factory of Mr. Tarwoto. The purpose of this study was to determine and analyze "The Effect of Sales Channels and Product Quality on Customer Loyalty at Mr Tarwoto's Tofu Factory". This study uses quantitative methods, by distributing questionnaires, the respondents who are used as samples are 110 respondents. The results of this study indicate that based on the results of the F test, it is found that the sales channel (X1) and product quality (X2) have a significant simultaneous effect on customer loyalty (Y) by comparing the F value with F because the F value is greater than the F value ( 135,439 > 3.08). F value 135,439 with a significant level (0.000<0.005). Then it is obtained that Ho is rejected and H3 is accepted, which means that this is done jointly between sales channels, product quality has a significant effect on customer loyalty. The value of Adjust R square is 0.712, this shows that the contribution of sales channel variables and product quality to loyalty is 0.712, which means that sales channels and product quality to purchasing decisions are 71.2% while 28.8% is influenced by other factors.